The return of the king being the third part of The lord of the rings - J. R. R. Tolkien (Ballantine Book U.S.A, 1965)
The prequel to The Lord of the Rings$1 (BThe Hobbits
Keywords: Baggins, Frodo (Fictitious character) -- Fiction; Middle Earth (Imaginary place); Science Fiction -- Science Fiction; Fantasy -- Fantasy